"El espanto" y "el aire": Síndromes Culturalmente Delimitados. Aproximación etnográfica al conocimiento local sobre los padecimientos de las madres indígenas Kichwas del Ecuador. - QUIROZ HIDROVO, ANA LUCÍA; RODRÍGUEZ-MARTÍN, DOLORS; LARREA-KILLINGER, CRISTINA (Cultura de los Cuidados, 2026)
Introduction: the cultural and social representations of the mothers of the Andean indigenous communities determine the type of illness and the therapeutic itinerary to follow. Objective: Identify the culturallybound syndromes described by Quechua women -- in Chugchilán-Ecuador--in the context of maternal and child care, as well as their causes, symptoms, and treatments. Methodology: The present ethnographic indígena. El conocimiento de los síndromes culturalmente study was carried out between September 16, 2020 and April 30, 2021; it included 14 indigenous women. The techniques applied were: participant observation and in-depth interviews. The observed scenarios were both the community and at home, accompanying mothers in their daily living activities. Results: The mothers' narratives show how they identify culturally-bound syndromes, from their system of representations. These illness respond to the local knowledge system --of the community itself-- and are not recognized by biomedicine. Of the culturally-bound syndromes shown in this community, two stood out: "el espanto" and "el aire". Based on maternal knowledge, it is described how they are delimited and classified, their prognosis or severity and the therapeutic itinerary or care process that they initiate. Conclusions: In "el espanto" and "el aire", social representatives of the Andean indigenous communities influence in the treatment decision, understanding that in biomedicine they will not find an answer for those types of conditions, but they using Traditional indigenous medicine they will. Knowledge of culturally-bound syndromes adds value to the application of intercultural care to indigenous people, either in their own original communities, or in the migratory contexts where they settle.